3D-Printed Self-Assembling Helical Models for Exploring Viral Capsid Structures - Donald Plante; Keegan Unzen; John R. Jungck (Biomimetics)
This work presents a novel application of additive manufacturing in the design of self-assembling helical viral capsids using 3D-printed components. Expanding on prior work with 3D-printed self-assembling spherical capsids, we developed helical models that integrate geometric parameters and magnetic interactions to mimic key features of the assembly process of helical viral capsids. Using dual-helix phyllotactic patterns and simplified electrostatic simulations, these models consistently self-assemble into a cylinder, providing unique insights into the structural organization and stability of helical capsids. This accessible 3D-printed approach demonstrates the potential of additive manufacturing for research in mesoscale self-assembling models and in the education of complex biological assembly processes, promoting hands-on exploration of viral architecture and self-assembly mechanisms.